Media Pembelajaran Tarian Jaipong Berbasis Android Menggunakan Multimedia Development Life Cycle - Dini Destiani Siti Fatimah; Raden Erwin Gunadhi Rahayu; Malik Dinar Jaelani (Jurnal Algoritma, 2022)
The influence of advanced technology is not only felt in the world of work, but also in the learning process, such as the existence of learning media. Learning media is a tool for interacting between educators and students in conducting learning and providing information so that an effective and efficient learning process can be created. With the existence of digital learning media, the learning process becomes more interesting, therefore this research has the goal of making a jaipong dance learning media application with the main content in the application, namely discussing jaipong dance. The methodology applied in making this application is the Multimedia Development Life Cycle (MDLC) with the stages included in it including concept, design, material collecting, assembly, testing and distribution. The results of the research that has been carried out are in the form of an android-based jaipong dance learning media application that can make the learning process more interesting. So that students who will use this learning media application can be more interested in getting to know the Jaipong dance culture because of the animated video features in the application.